GRUNT TOʻGʻONLARNING MUSTAHKAMLIGI HAMDA ULARDA KUZATILADIGAN BUZULISH VA AVARIYA HOLATLARI - Kupaysinov Dostonbek Xusnidin o‘g‘li; Kupaysinov Dostonbek Xusnidin o‘g‘li (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, the existing hydropower facilities and dams in the Republic are organized and operating conditions, groups and lists of the main works performed by the service of the operation of hydropower facilities, monitoring of the technical conditions of pressure-generating ground structures, reconstruction of dams and hydropower facilities issues have been considered.